The Impact of Gross Domestic Product Response to the Money Supply Shock in the Iraqi Economy for the Period (2004-2021) - Wahaib Abdallah , Ali; Siham Dawood, Sameer (Journal of Economics and Administrative Sciences, 2023)
The research aims to clarify the response of the GDP to the M1 shock. It includes access to the results using standard methods, where the standard model was built according to quarterly data using the program STATA 17. According to the joint integration model ARDL, the research found a long-term equilibrium positive for the relationship between GDP and the money supply in Iraq, as the change in the money supply by a certain percentage will lead to a change in GDP by about 71% of that percentage. In the event of a shock in the Iraqi economy, the impact of the M1 will differ from what it was before the shock, as the shock will increase its effectiveness towards GDP by about 10% more than before the shock. At the same time, the relationship between them remains positive. One of the most important recommendations is to work to achieve a proportional balance between the money supply and GDP. This is done through the control of monetary policy to reach a real balance between the monetary and commodity sectors. It contributes to addressing the chronic imbalances of most economic sectors, especially in productivity and its vulnerability to monetary economic shocks.Paper type: Research paper.